An iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio and a preparation method thereof

By adopting a five-layer cladding structure and optimization process on the nanocrystalline magnetic powder core, the problems of impurities introduction and instability of the insulating layer in the preparation of nanocrystal magnetic powder core are solved, and iron-based nanometers with high magnetic permeability and high rectangular ratio are achieved Crystal soft magnetic powder core is suitable for high frequency and high temperature applications in the field of electronic power.

CN115064332BActive Publication Date: 2024-12-17GUANGDONG INST OF NEW MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210755528.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-06-29
Publication Date
2024-12-17
Estimated Expiration
2042-06-29

AI Technical Summary

Technical Problem

The existing nanocrystalline magnetic powder core is prone to introduce impurities during the preparation process, the powder is uneven and difficult to cover, resulting in high loss of magnetic powder core and unstable insulation layer, which cannot meet the high frequency and high temperature requirements in the electronic and electrical field. The rectangle is relatively low, which is limited. Its application.

Method used

Using a five-layer cladding structure, including a passivation layer, a SiO2 layer, an Al2O3 layer, a stearate layer and a silicone resin layer, the permeability and rectangular ratio of the magnetic powder core are improved through these layers and the eddy current is reduced. Magnetic loss and optimize the performance of the magnetic powder core by controlling the pressing pressure and heat treatment process.

Benefits of technology

It realizes the high magnetic permeability and high rectangular ratio of iron-based nanocrystal soft magnetic powder core, reduces eddy current magnetic loss, improves corrosion resistance and resistivity, ensures frequency stability and high temperature performance, and is suitable for the field of electronic power.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115064332B_ABST
    Figure CN115064332B_ABST
Patent Text Reader

Abstract

The invention discloses an iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio and a preparation method thereof, belonging to the technical field of alloy soft magnetic powder core. The invention coats a passivation layer, a SiO2 layer, an Al2O3 layer, a stearate layer and a silicone resin layer on the surface of the iron-based nanocrystalline. Through the joint action of the five coating layers, not only the direct contact between the iron-based nanocrystalline magnetic powders is avoided, but also the compaction density and core resistivity of the iron-based nanocrystalline soft magnetic powder core are improved, thereby reducing eddy current magnetic loss; at the same time, by controlling the pressing pressure and heat treatment process conditions, the iron-based nanocrystalline soft magnetic powder core has the characteristics of high corrosion resistance, high resistivity and high densification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of alloy soft magnetic powder cores, and in particular to an iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio and a preparation method thereof. Background Art

[0002] Iron-based amorphous nanocrystalline soft magnetic alloys have been widely used in various transformers, sensors, switching power supplies and other fields due to their high saturation magnetic induction intensity, high magnetic permeability, low coercive force and low loss. However, with the development of the electronic power industry, electronic devices have gradually become smaller, more high-frequency and integrated, and magnetic powder cores are needed to meet working requirements; metal soft magnetic powder cores are a kind of soft magnetic material made by pressing magnetic powders coated with insulating media in a certain proportion and evenly mixing them. There is an insulating layer between adjacent magnetic powders, and the magnetic powders are separated by non-magnetic insulating materials. The particles are insulated from each other. Therefore, the eddy current loss of the magnetic powder core is very small at medium and high frequencies, and its magnetic permeability is small but has good linearity. At the same time, because the particle size of the metal magnetic powder is small, there is basically no skin effect on the surface of the magnetic powder, and the magnetic permeability changes relatively stably with frequency; the magnetic powder core combines the advantages of insulating agents and metal powders, so that it has high saturation magnetic induction intensity and high resistivity, which broadens the scope of use of traditional soft magnetic materials. At the same time, because it uses powder metallurgy technology for pressing and molding, it can prepare various complex shapes such as C-type, E-type, U-type, ring-shaped, etc. The flexible shape design and good frequency stability give it broad market development prospects.

[0003] At present, the magnetic powder core products on the market mainly include iron powder core, sendust powder core, iron nickel powder core, high magnetic flux powder core and new amorphous nanocrystalline magnetic powder core. 73.5 Si 13.5Nanocrystalline magnetic powder cores represented by B9Cu1Nb3 alloy have higher saturation magnetic induction intensity, high magnetic permeability and good stability compared to other magnetic powder cores, and are widely used in the electronics industry. The process flow is roughly as follows: preparation of magnetic powder, insulation coating process, pressing and annealing treatment; however, amorphous and nanocrystalline magnetic powders are currently prepared by strip crushing, which easily introduces impurities during ball milling, resulting in uneven powder composition, and the obtained powders are mostly flakes with sharp edges and irregular shapes, which are difficult to coat, affecting the insulation effect of the magnetic powder surface and resulting in high losses in the magnetic powder core; at the same time, coating agents with a relatively single composition will cause the insulation coating of the magnetic powder core to be unstable. For example, the magnetic powder core coated with an organic insulation layer has low thermal stability and cannot be subjected to high-temperature annealing treatment, and the mechanical properties and related magnetic properties of the obtained magnetic powder core cannot meet the application requirements. The brittleness of the inorganic coating layer limits the high-density magnetic powder core obtained in the pressing process; the organic-inorganic composite coating method retains the advantages of both organic and inorganic, so more and more research is being done on it, but the poor control of factors such as the uniformity and thickness of the multi-layer coating affects the magnetic properties of the magnetic powder core; in the preparation process of nanocrystalline magnetic powder cores, the insulation coating technology is the most important and most complex link in the preparation process of amorphous and nanocrystalline magnetic powder cores. The selection of insulating agents, the thickness and uniformity of the coating layer directly affect the magnetic permeability, rectangular ratio, frequency stability and other soft magnetic properties of the magnetic powder core; in addition, the pressing pressure and annealing temperature are also important factors affecting the soft magnetic properties of the nanocrystalline magnetic powder core. At present, the preparation of nanocrystalline magnetic powder cores generally makes the rectangular ratio of the nanocrystalline magnetic powder cores relatively low, which is not conducive to its wider application in the field of electronic power.

[0004] Therefore, developing an iron-based nanocrystalline magnetic powder core with high magnetic permeability and high rectangular ratio is one of the current research hotspots in amorphous nanocrystalline soft magnetic powder core materials. Summary of the invention

[0005] The object of the present invention is to overcome the above-mentioned deficiencies of the prior art and to provide an iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the technical solution adopted by the present invention is: an iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio, wherein the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio is composed of iron-based nanocrystals and five coating layers, and the coating layers are respectively a passivation layer, a SiO2 layer, an Al2O3 layer, a stearate layer and a silicone resin layer from the inside to the outside.

[0007] The present invention coats the surface of the iron-based nanocrystal with five coating layers. The passivation layer can form a passivation film on the surface of the iron-based nanocrystal magnetic powder, and the passivation film plays a role in protecting the iron-based nanocrystal magnetic powder in the subsequent coating process; the SiO2 layer has the characteristics of high thermal stability and high resistivity. It is attached to the surface of the passivated iron-based nanocrystal magnetic powder, which can avoid direct contact between the magnetic powders and also increase the resistivity between the magnetic powders, thereby achieving the purpose of reducing eddy current magnetic loss; the Al2O3 layer is a high-temperature resistant material, and its strength and adhesion are better than most metal oxides, which can ensure that it will not be punctured by the magnetic powder in the subsequent magnetic powder core pressing and molding process, and can also promote the formation of a highly densified magnetic powder core structure. ; and it has a high resistivity, which can effectively improve the soft magnetic properties of the iron-based nanocrystalline soft magnetic powder core; on the one hand, the stearate layer can be used as a lubricant to increase the compaction density of the subsequent magnetic powder in the pressing process to form a highly densified magnetic powder core structure, on the other hand, the stearate can also be decomposed in the subsequent heat treatment process to form oxides on the surface of the magnetic powder, thereby increasing the core resistivity of the magnetic powder core, thereby achieving the purpose of reducing eddy current magnetic loss; the silicone resin layer can be used as a binder to make the magnetic powder core easier to be pressed and formed, on the other hand, the silicone resin can form SiO2 on the surface of the magnetic powder during the subsequent heat treatment process, thereby further increasing the core resistivity of the magnetic powder core, thereby achieving the purpose of reducing eddy current magnetic loss.

[0008] The inventors further discovered that the magnetic permeability and rectangular ratio of the iron-based nanocrystalline soft magnetic powder core can be effectively improved by using the above five coating layers.

[0009] Another object of the present invention is to provide a method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio, comprising the following steps:

[0010] S1. Pretreatment: crushing the iron-based nanocrystals into flaky powder to obtain nanocrystalline magnetic powder;

[0011] S2, a layer of coating: dissolving a strong acid or a medium-strong acid in ethanol or acetone to form a mixed solution, and adding the nanocrystalline magnetic powder to stir, and after the ethanol or acetone is completely volatilized, a passivation layer is formed on the surface of the nanocrystalline magnetic powder, and the passivated nanocrystalline magnetic powder is obtained;

[0012] S3, second layer coating: add the passivated nanocrystalline magnetic powder into an ethanol aqueous solution, stir for 5-30 min at a temperature of 50-70°C, then add a silane coupling agent and continue stirring for 0.5-1h, thus completing the second layer coating of the nanocrystalline magnetic powder;

[0013] S4, three-layer coating: dissolving aluminum isopropoxide in an ethanol aqueous solution and stirring at a temperature of 80-100° C. until the solution is uniform and transparent, then dropping nitric acid into the uniform transparent solution until the pH of the solution is 3-4, then adding the magnetic powder obtained in step S3, continuing to drop deionized water, and finally washing the magnetic powder with anhydrous ethanol and drying at 80-100° C., thus completing the third layer coating of the nanocrystalline magnetic powder;

[0014] S5, four-layer coating: adding the magnetic powder obtained in step S4 to an ethanol or acetone solution of stearate, stirring until the ethanol or acetone is completely volatilized, so that the stearate is evenly coated on the surface of the magnetic powder obtained in step S4, that is, the fourth layer coating of the nanocrystalline magnetic powder is completed;

[0015] S6, five-layer coating: adding the magnetic powder obtained in step S5 to an ethanol or acetone solution of an organic silicone resin, and stirring until the ethanol or acetone is completely volatilized, thus completing the fifth layer coating of the nanocrystalline magnetic powder;

[0016] S7, heat treatment: pressing the magnetic powder obtained in step S6 to obtain an amorphous composite soft magnetic powder core, and then heat treating the amorphous composite magnetic powder core in a nitrogen atmosphere to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio.

[0017] Preferably, in step S1, the iron-based nanocrystals are Fe 73.5 Si 13.5 B9Cu1Nb3.

[0018] Preferably, in step S1, the iron-based nanocrystals are crushed to a median diameter D by ball milling. 50 70-80μm.

[0019] Preferably, in step S2, the strong acid or medium-strong acid is nitric acid or phosphoric acid.

[0020] Preferably, in step S2, the mass ratio of strong acid or medium-strong acid to nanocrystalline magnetic powder is 1:200-1000.

[0021] Preferably, in step S3, the silane coupling agent is aminopropyltriethoxysilane (APTES).

[0022] Preferably, in step S3, the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 1:2.

[0023] Preferably, in step S3, the concentration of the passivated nanocrystalline magnetic powder dissolved in the ethanol aqueous solution is 0.3-0.35 g / ml.

[0024] Preferably, in step S3, the mass ratio of the silane coupling agent to the passivated nanocrystalline magnetic powder is 1:10-20.

[0025] Preferably, in step S4, the volume ratio of anhydrous ethanol to deionized water in the ethanol aqueous solution is 2-6:200-400.

[0026] Preferably, in step S4, the concentration of aluminum isopropoxide in the ethanol aqueous solution is 0.0002-0.005 g / ml.

[0027] Preferably, in step S4, the stirring speed of dissolving aluminum isopropoxide in the ethanol aqueous solution is 20-80 rpm, and the stirring time is 0.5-1 h.

[0028] Preferably, in step S4, the mass ratio of aluminum isopropoxide to the magnetic powder obtained in S3 is 1:10-20.

[0029] Preferably, in step S5, the stearate is zinc stearate.

[0030] Preferably, in step S5, the mass ratio of stearate to magnetic powder is 1:50-200.

[0031] Preferably, in step S6, the mass ratio of the silicone resin to the magnetic powder obtained in S5 is 1:50-200.

[0032] It should be noted that in steps S2, S5 and S6 of the present invention, the volume of ethanol or acetone only needs to completely cover the nanocrystalline magnetic powder.

[0033] Preferably, in step S7, the pressing pressure is 1000-1500 MPa. The low pressing pressure greatly reduces the loss of the pressing mold and does not affect the soft magnetic properties of the amorphous composite soft magnetic powder core.

[0034] Preferably, in step S7, the heat treatment process is specifically as follows: placing the amorphous composite soft magnetic powder core in a tubular furnace, exhausting the air in the furnace, then introducing nitrogen, first heating to 480-510°C, keeping warm for 15-60 minutes, with a heating rate of 1-20°C / min, and then heating to 540-560°C, with a heating rate of 1-5°C / min; when reaching 540-560°C, stop heating, open the furnace of the tubular furnace and increase the nitrogen flow rate, so as to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio; the present invention increases the heat dissipation in the furnace by removing the furnace heating heat source, and at the same time takes away a large amount of heat of the iron-based amorphous nanocrystalline soft magnetic composite powder core in the furnace cavity through nitrogen to ensure cooling to room temperature. The heat treatment process of the present invention can precipitate a large number of α-Fe(Si) nanocrystals on the amorphous matrix, thereby obtaining the iron-based amorphous nanocrystalline soft magnetic composite powder core. The heat treatment temperature can determine the content of the α-Fe(Si) nanocrystals, and the percentage of the α-Fe(Si) nanocrystalline phase and the amorphous matrix phase is also the determining factor of the magnetic properties of the powder core. Therefore, the present invention needs to strictly control the heat treatment temperature to induce the amorphous matrix to undergo a crystallization reaction, and reduce the insulation time of the material to reduce the magnetic loss of the insulating coating layer in the high temperature environment, ultimately greatly improving the magnetic permeability and remanence ratio of the magnetic powder core, and having better frequency stability.

[0035] The beneficial effects of the present invention are as follows: the present invention coats the surface of the iron-based nanocrystal with a passivation layer, a SiO2 layer, an Al2O3 layer, a stearate layer and a silicone resin layer. Through the joint action of the five coating layers, not only the direct contact between the iron-based nanocrystalline magnetic powders is avoided, but also the compaction density and core resistivity of the iron-based nanocrystalline soft magnetic powder core are improved, thereby reducing eddy current magnetic loss; at the same time, by controlling the pressing pressure and heat treatment process conditions, the iron-based nanocrystalline soft magnetic powder core has the characteristics of high corrosion resistance, high resistivity and high densification; under the low pressing pressure of 1000-1500Mpa and the test conditions of Bm=0.1T and 50kHz, the magnetic permeability of the iron-based nanocrystalline soft magnetic powder core of the present invention can be as high as 80, the rectangular ratio can be as high as 0.016, and it shows good frequency stability in the frequency range of 25-300kHz. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a magnetic permeability-frequency diagram of the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio described in Examples 1-3 and Comparative Examples 1-2.

[0037] Figure 2 This is a magnetic rectangular ratio-frequency diagram of the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio described in Examples 1-3 and Comparative Examples 1-2. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0039] Example 1

[0040] An embodiment of an iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio described in the present invention, the preparation method of the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio described in this embodiment comprises the following steps:

[0041] S1. Pretreatment: using alloy composition of Fe 73.5 Si 13.5 The iron-based nanocrystals of B9Nb3Cu1 were crushed to a median diameter D by ball milling. 50 70-80μm, that is, nanocrystalline magnetic powder;

[0042] S2, one layer of coating: dissolve 1g of phosphoric acid in acetone to form a phosphate acetone solution, add 200g of nanocrystalline magnetic powder into the phosphate acetone solution; the volume of the acetone solution needs to completely cover the surface of the magnetic powder, slowly stir at a stirring speed of 60rmp until the acetone is completely volatilized, at this time, a thin phosphate passivation layer is formed on the surface of the magnetic powder;

[0043] S3, second layer coating: add the passivated nanocrystalline magnetic powder into 600 ml of 33.3% ethanol aqueous solution, transfer the mixed solution to a round-bottom flask and stir at 50°C for 30 min, then drop 0.1 g of APTES into the round-bottom flask, and continue to stir slowly at 50°C for 1 h to complete the second layer coating of the nanocrystalline magnetic powder;

[0044] S4, three-layer coating: first, dissolve 0.05g of aluminum isopropoxide in 20.3ml of ethanol aqueous solution, transfer the mixed solution to a round-bottom flask and stir at 80°C at 80rpm for 1h to obtain a uniform transparent solution, then add nitric acid to the uniform transparent solution until the pH of the solution is 4, add the magnetic powder obtained in step S3, and then use a constant pressure funnel to drop 0.3ml of deionized water into the round-bottom flask drop by drop, after all the deionized water is added, cool to room temperature with the furnace, wash the magnetic powder with anhydrous ethanol for at least three times after cooling, and dry it at 80°C, thus completing the third layer coating of the nanocrystalline magnetic powder;

[0045] S5, four-layer coating: dissolve 0.25g zinc stearate in acetone, add the magnetic powder obtained in step S4 to the zinc stearate / acetone solution, the acetone content must completely cover the surface of the magnetic powder, slowly stir at a speed of 50rpm until the acetone is completely volatilized, so that the zinc stearate is evenly coated on the surface of the nanocrystalline magnetic powder, that is, the fourth layer of coating of the nanocrystalline magnetic powder is completed;

[0046] S6, five-layer coating: 1 g of organic silicone resin is fully dissolved in acetone, and the magnetic powder obtained in step S5 is added to the acetone solution of the organic silicone resin. The organic silicone resin acetone solution must completely cover the surface of the magnetic powder, and the mixture is slowly stirred at a speed of 50 rpm until the acetone is completely volatilized, thus completing the fifth layer coating of the nanocrystalline magnetic powder;

[0047] S7, heat treatment: the magnetic powder obtained in step S6 is pressed in a mold to form an amorphous composite soft magnetic powder core, and the pressing pressure is 1500MPa; then, the obtained amorphous composite magnetic powder core is subjected to an appropriate heat treatment process: the sample powder core is placed in a tubular furnace, and the air in the furnace is first evacuated to exhaust the vacuum, and then nitrogen is introduced to make the sample heat treated in a nitrogen atmosphere, first the temperature is raised to 510°C and kept warm for 60 minutes, and the heating rate is 10°C / min, and then the temperature is raised to the final temperature of 560°C, and the heating rate is 1°C / min. When the final temperature is reached, the heating is immediately stopped, the furnace is opened, and the nitrogen flow rate is increased to cool to room temperature, so as to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio.

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:1000, and the stirring speed is 30 rpm; in step S3, the mixed solution of the passivated nanocrystalline magnetic powder and the ethanol aqueous solution is stirred at a temperature of 70°C for 10 min, and APTES is added dropwise and then slowly stirred at a temperature of 70°C for 0.5 h; in step S4, the mass ratio of aluminum isopropoxide to magnetic powder is 1:20, aluminum isopropoxide is dissolved in the ethanol aqueous solution, and stirred at a rate of 40 rpm at a temperature of 90°C for 0.5 h to obtain a uniform transparent solution, and then nitric acid is added dropwise to the uniform transparent solution until the pH of the solution is 3, and the magnetic powder is dried at a temperature of 100°C after being washed with anhydrous ethanol. ; In step S5, the mass ratio of zinc stearate to magnetic powder is 1:200, and the stirring speed is 40rmp; in step S6, the mass ratio of silicone resin to magnetic powder obtained in S5 is 1:50, and the stirring speed is 40rmp; in step S7, the pressing pressure is 1000MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is discharged, and then nitrogen is introduced, the temperature is first raised to 480°C, kept warm for 15 minutes, the heating rate is 10°C / min, and then the temperature is raised to 550°C, and the heating rate is 5°C / min; when it reaches 550°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, so as to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio.

[0050] Example 3

[0051] The difference between this embodiment and embodiment 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:400, and the stirring speed is 50 rpm; in step S3, the mixed solution of the passivated nanocrystalline magnetic powder and the ethanol aqueous solution is stirred at a temperature of 60°C for 20 min, and APTES is added dropwise and then slowly stirred at a temperature of 70°C for 0.7 h; in step S4, the mass ratio of aluminum isopropoxide to magnetic powder is 1:15, aluminum isopropoxide is dissolved in the ethanol aqueous solution, and stirred at a rate of 60 rpm at a temperature of 100°C for 1 h to obtain a uniform transparent solution, and then nitric acid is added dropwise to the uniform transparent solution until the pH of the solution is 3.5, and the drying temperature of the magnetic powder after washing with anhydrous ethanol is 90°C; In step S5, the mass ratio of zinc stearate to magnetic powder is 1:150, and the stirring speed is 50 rmp; in step S6, the mass ratio of silicone resin to magnetic powder obtained in S5 is 1:100, and the stirring speed is 50 rmp; in step S7, the pressing pressure is 1300 MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is exhausted, and then nitrogen is introduced, the temperature is first raised to 500°C, kept warm for 30 minutes, the heating rate is 20°C / min, and then the temperature is raised to 550°C, and the heating rate is 3°C / min; when reaching 550°C, the heating is stopped, the furnace of the tubular furnace is opened and the nitrogen flow rate is increased, so as to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio.

[0052] Comparative Example 1

[0053] The difference between this comparative example and Example 1 is that: in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:100, and the stirring speed is 50 rpm; in step S3, the mixed solution of the passivated nanocrystalline magnetic powder and the ethanol aqueous solution is stirred at room temperature for 30 min, and APTES is added dropwise and then slowly stirred at room temperature for 1 h; in step S4, the mass ratio of aluminum isopropoxide to magnetic powder is 1:5, aluminum isopropoxide is dissolved in the ethanol aqueous solution, and stirred at a rate of 60 rpm for 1 h at a temperature of 90°C to obtain a uniform transparent solution, and then nitric acid is added dropwise to the uniform transparent solution until the pH of the solution is 5, and the magnetic powder is washed with anhydrous ethanol and dried at a temperature of 90℃; in step S5, the mass ratio of zinc stearate to magnetic powder is 1:30, and the stirring speed is 50rmp; in step S6, the mass ratio of silicone resin to magnetic powder obtained in S5 is 1:30, and the stirring speed is 50rmp; in step S7, the pressing pressure is 1600MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is discharged, and then nitrogen is introduced, the temperature is first raised to 500℃, kept warm for 30min, the heating rate is 20℃ / min, and then the temperature is raised to 570℃, the heating rate is 1℃ / min; when it reaches 570℃, the heating is stopped, and the furnace is cooled to room temperature to obtain the iron-based nanocrystalline soft magnetic powder core.

[0054] Comparative Example 2

[0055] The difference between this comparative example and Example 1 is that: it does not include steps S3 and S4, and in step S2, the mass ratio of phosphoric acid to nanocrystalline magnetic powder is 1:50, and the stirring speed is 50rpm; in step S5, the mass ratio of zinc stearate to magnetic powder is 1:30, and the stirring speed is 50rmp; in step S6, the mass ratio of silicone resin to the magnetic powder obtained in S5 is 1:30, and the stirring speed is 50rmp; in step S7, the pressing pressure is 1600MPa, the amorphous composite soft magnetic powder core is placed in a tubular furnace, the air in the furnace is discharged, and then nitrogen is introduced, the temperature is first raised to 500°C, kept warm for 30min, the heating rate is 20°C / min, and then the temperature is raised to 550°C, the heating rate is 1°C / min; when reaching 550°C, the heating is stopped, and the furnace is cooled to room temperature to obtain the iron-based nanocrystalline soft magnetic powder core.

[0056] Effect example

[0057] The magnetic permeability and rectangular ratio of the iron-based nanocrystalline soft magnetic powder cores described in Examples 1-3 and Comparative Examples 1-2 were measured using a BH analyzer (IWATSU, SY-8219). The test conditions were: Bm=0.1T, f=50kHz. The test results are shown in Table 1 below.

[0058] Table 1

[0059] sample Magnetic Permeability Rectangle Ratio Example 1 74.4 0.01609 Example 2 80.3 0.01586 Example 3 78.2 0.01781 Comparative Example 1 68.8 0.01425 Comparative Example 2 66.2 0.01275

[0060] It can be seen from Table 1 that the iron-based nanocrystalline soft magnetic powder cores in Examples 1-3 have magnetic permeabilities greater than 75 and rectangular ratios greater than 0.015 under the test conditions of Bm=0.1T and 50kHz, respectively, and have the advantages of high magnetic permeability and high rectangular ratio. However, in Comparative Examples 1-2, since the stirring speed or the mass ratio of each component in the process of preparing the coating layer on the surface of the nanocrystalline magnetic powder exceeds the scope of the present invention, the final iron-based nanocrystalline soft magnetic powder cores have magnetic permeabilities less than 70 and rectangular ratios less than 0.015 under the test conditions of Bm=0.1T and 50kHz, and since only three layers of coating were performed on the iron-based nanocrystals in Comparative Example 2, the final magnetic permeability was only 66.2 and the rectangular ratio was only 0.01275, which are quite different from those of the embodiments.

[0061] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an iron-based nanocrystalline soft magnetic powder core having high magnetic permeability and high rectangular ratio, characterized in that: The following steps are involved: S1. Pretreatment: crushing the iron-based nanocrystals into flaky powder to obtain nanocrystalline magnetic powder; S2, a layer of coating: dissolving a strong acid or a medium-strong acid in ethanol or acetone to form a mixed solution, and adding the nanocrystalline magnetic powder to stir, and after the ethanol or acetone is completely volatilized, a passivation layer is formed on the surface of the nanocrystalline magnetic powder, and the passivated nanocrystalline magnetic powder is obtained; S3, second layer coating: add the passivated nanocrystalline magnetic powder into an ethanol aqueous solution, stir for 5-30 min at a temperature of 50-70°C, then add a silane coupling agent and continue stirring for 0.5-1h, thus completing the second layer coating of the nanocrystalline magnetic powder; S4, three-layer coating: dissolving aluminum isopropoxide in an ethanol aqueous solution and stirring at a temperature of 80-100° C. until the solution is uniform and transparent, then dropping nitric acid into the uniform transparent solution until the pH of the solution is 3-4, then adding the magnetic powder obtained in step S3, continuing to drop deionized water, and finally washing the magnetic powder with anhydrous ethanol and drying at 80-100° C., thus completing the third layer coating of the nanocrystalline magnetic powder; S5, four-layer coating: adding the magnetic powder obtained in step S4 to an ethanol or acetone solution of stearate, stirring until the ethanol or acetone is completely volatilized, so that the stearate is evenly coated on the surface of the magnetic powder obtained in step S4, that is, the fourth layer coating of the nanocrystalline magnetic powder is completed; S6, five-layer coating: adding the magnetic powder obtained in step S5 to an ethanol or acetone solution of an organic silicone resin, and stirring until the ethanol or acetone is completely volatilized, thus completing the fifth layer coating of the nanocrystalline magnetic powder; S7, heat treatment: pressing the magnetic powder obtained in step S6 to obtain an amorphous composite soft magnetic powder core, and then heat treating the amorphous composite magnetic powder core in a nitrogen atmosphere to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio; The iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio is composed of iron-based nanocrystalline and five coating layers, wherein the coating layers are respectively a passivation layer, a SiO2 layer, an Al2O3 layer, a stearate layer and a silicone resin layer from the inside to the outside; In the step S7, the pressing pressure is 1000-1500MPa; the specific heat treatment process is: placing the amorphous composite soft magnetic powder core in a tubular furnace, heating it to 480-510°C in a nitrogen atmosphere, keeping it warm for 15-60 minutes, then continuing to heat it to 540-560°C and stopping heating, so as to obtain the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high rectangular ratio.

2. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In step S1, the iron-based nanocrystals are Fe 73.5 Si 13.5 B9Cu1Nb3.

3. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In the step S3, the silane coupling agent is aminopropyltriethoxysilane.

4. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In the step S3, the mass ratio of the silane coupling agent to the passivated nanocrystalline magnetic powder is 1:10-20.

5. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In the step S4, the mass ratio of aluminum isopropoxide to the magnetic powder obtained in S3 is 1:10-20.

6. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In the step S5, the stearate is zinc stearate.

7. The method for preparing the iron-based nanocrystalline soft magnetic powder core with high magnetic permeability and high squareness ratio according to claim 1, characterized in that: In the step S5, the mass ratio of stearate to magnetic powder is 1:50-200.